Fortellingens betydning for å fremme livsmotet i møte med alvorlig sykdom - Kjersti Sunde Mæhre (Septentrio Academic Publishing, 2019)
The importance of the story to promote hope and life courage in the face of serious illness In connection with my PhD (Mæhre, 2017), I conducted qualitative interviews with five critically ill patients in an enhanced ward of a nursing home, based on the Coordination Reform. The purpose of the interviews was to increase understanding of patient experiences of the ward, and their perceived challenges and needs for assistance. The research method was a hermeneutic-phenomenological approach. The essay is based on one of the patient interviews, which has been rewritten as a narrative. This narrative emphasizes how the patient has fought against her illness, and her need to be seen as herself as a person and not understood in terms of a diagnosis. The illness narrative becomes part of her life story. The article highlights opportunities for narratives in the face of serious illness. The narrative reveals how a changed life situation, despite severe illness, can add courage and joy to life, but also how it can lead to hopelessness, doubt, and uncertainty.